Neural substrates of suicide and suicidal behaviour: from a neuroimaging perspective - Balcioğlu, Yasin Hasan; Kose, Samet (Taylor and Francis Ltd., 2018)
In this article, we have reviewed neuroimaging studies on the neural circuitry associated with suicidal behaviour in order to identify the neural substrates of suicidal behaviour. The Medline and ScienceDirect databases were comprehensively and systematically searched and articles published from 1990 through 2017 were reviewed. Reviewed brain-imaging modalities included structural magnetic resonance imaging, diffusion tensor imaging, positron-emission tomography, single-photon emission computed tomography, resting-state functional Imaging, and functional magnetic resonance imaging. Although subject characteristics and imaging methods vary across studies, convergent findings involving the structure and function of frontostriatal network and fronto-limbic structures, and the serotonergic system were identified. These neuroimaging studies of suicide behaviour have provided crucial information on the neural circuitry associated with suicide risk. Future studies examining neural changes associated with before and after pharmacologic and behavioural interventions would be instrumental in suicide risk reduction.
Keywords: Magnetic resonance imaging; neuroimaging; positron-emission tomography; single-photon emission computed tomography; suicide